Prospects for the Development of Domestic Gastronomic Tourism in Conditions of Restrictions Caused by the COVID-19 Pandemic - SOKOLOVA, Antonina Pavlovna; SERYSHEV, Roman Viktorovich; LIVSON, Maya; BARANOV, Ekaterina A.; ZUNDE, Viktoria Viktorovna (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
The development of the domestic tourism market in the conditions of existing restrictions in the world due to the COVID-19 pandemic is shaping the tourism industry in a new way as an integral attribute of modern society. Domestic tourism is gaining an increasing influence on the economy of many countries, as the domestic tourism industry provides an increase in gross domestic product, helps to overcome unemployment at the regional level, and contributes to the development of infrastructure facilities. The purpose of the article is to analyze the prospects for the development of domestic gastronomic tourism in conditions of restrictions caused by the COVID-19 pandemic. The article focuses on the main aspects of gastronomic tourism. The concept and essence of gastronomic tourism have been clarified , the classification of varieties of gastronomic tourism has been presented, SWOT analysis of gastronomic tourism in Russia has been carried out, the positive consequences of the development of gastronomic tourism in Russia and the world during the lifting of restrictions caused by COVID-19 have been determined. It has been concluded that gastronomic tourism is one of the key factors of the tourist attractiveness of the territory, is an important component of the sustainable development of the tourism sector, capable of generating significant economic and social benefits for the participants of the domestic tourism market . In this connection, today the infrastructure of gastronomic tourism in Russia requires expansion, which will be possible due to the support from the state, the creation of a favorable investment climate .